A kind of nitrogen-doped ginkgo leaf biomass fluorescent carbon quantum dots and its preparation method and application in Cr (VI) detection
Patent Information
- Application Number
- CN202611080776.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-21
- Publication Date
- 2026-10-27
AI Technical Summary
[0033]与现有技术相比,本发明的优点如下:(1)本发明首次以银杏叶为碳源、间苯二胺为氮源,制备出在365 nm的紫外灯下呈绿色荧光的长发射波长荧光碳纳米材料。(2)银杏叶属于天然农林废弃物,来源广泛、零成本、绿色可再生、无二次污染,替代了传统化工合成碳源,制备工艺绿色环保、成本低廉。辅以间苯二胺精准氮掺杂改性,可有效调控碳量子点表面官能团与电子结构,极大提升材料的荧光量子产率、光学稳定性,材料荧光性能优异、储存稳定性强,有效解决了传统碳量子点荧光弱、稳定性差的技术痛点。(3)本发明构建了一个独特的跟踪Cr(VI)的平台。制备的基于氮参杂银杏叶生物质荧光碳量子点表面富含氨基、羟基等活性官能团,可与Cr (VI)发生特异性电子转移作用,从而实现对水体中Cr (VI)的专一性识别;该碳量子点荧光信号随Cr (VI) 浓度升高呈现规律性猝灭变化,依托荧光强度与离子浓度间良好的线性拟合关系,可完成水样中Cr (VI)的快速、精准定量分析,且具有较强抗干扰能力。
Smart Images

Figure CN122978956A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of fluorescent nanomaterials technology, and particularly relates to a nitrogen-doped fluorescent carbon quantum dots based on Ginkgo biloba biomass, its preparation method, and its application in Cr(VI) detection. Background Technology
[0002] Water pollution is becoming increasingly serious, necessitating the development of highly sensitive, rapid, portable, and low-cost pollutant detection methods. Heavy metals are highly toxic and difficult to biodegrade, easily accumulating along the food chain. Chromium is a typical high-risk heavy metal in the aquatic environment. Chromium mainly exists in two valence states, Cr(III) and Cr(VI). Excessive exposure can induce carcinogenesis and damage the digestive, respiratory, and immune organs. The US EPA sets the limit for total chromium in drinking water at only 0.1 mg / L. However, industrial wastewater discharge from paint, leather tanning, and electroplating industries is a major source of excessive Cr(VI) levels in water bodies. Therefore, establishing efficient methods for monitoring Cr(VI) in water bodies is of great significance.
[0003] Carbon quantum dots (CDs), as zero-dimensional carbon nanomaterials with a particle size of less than 10 nm, possess excellent photoelectric properties and are ideal media for green fluorescence sensing. Biomass carbon sources are low-cost, environmentally friendly, and align with sustainable development principles. They also possess heteroatoms and aromatic frameworks, allowing for in-situ doping in a single step to modulate the optical properties of the carbon dots. Existing research primarily utilizes biomass such as fruit peels, tea leaves, and microorganisms to prepare sensing carbon quantum dots; reports on the synthesis of carbon dots using ginkgo leaves as a precursor are extremely rare.
[0004] This study synthesized green fluorescent carbon dots using ginkgo leaves as the carbon source and m-phenylenediamine as the nitrogen source via a hydrothermal method. The carbon dots exhibited excellent selectivity and sensitivity to Cr(VI). Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention utilizes a one-step hydrothermal method to prepare carbon quantum dots with fluorescent properties and verifies that they can be widely used as fluorescent detectors for detecting Cr(VI).
[0006] This invention is specifically achieved through the following technical solutions:
[0007] The first aspect of the present invention provides a fluorescent carbon quantum dot, wherein the optimal excitation wavelength of the carbon quantum dot is 420 nm, the optimal emission wavelength is 514 nm, and it exhibits green fluorescence under a 365 nm ultraviolet lamp.
[0008] A second aspect of this invention provides a method for preparing nitrogen-doped Ginkgo biloba leaf biomass fluorescent carbon quantum dots, comprising the following steps:
[0009] Step 1: Take the washed ginkgo leaves, dry them in an oven at a specific temperature for a certain period of time, grind them into powder and sieve them.
[0010] Step 2: Place the ginkgo leaf powder and amino-rich raw materials in a beaker according to a certain feeding ratio, and disperse them evenly by ultrasonication.
[0011] Step 3: Transfer the above mixture to a Teflon-lined reactor for hydrothermal reaction;
[0012] Step 4: Centrifuge the obtained dark yellow carbon quantum dot dispersion and collect the supernatant;
[0013] Step 5: Place the obtained solution into a dialysis bag, pour in ultrapure water and dialyze to remove impurities, obtaining a yellow solution;
[0014] Step 6: Place the obtained solution in a vacuum freeze dryer to freeze dry, and obtain purified nitrogen-doped Ginkgo biloba biomass fluorescent carbon quantum dots.
[0015] In the above-mentioned nitrogen-doped Ginkgo biloba biomass fluorescent carbon quantum dots, the drying temperature in step 1 is 110°C.
[0016] In the above-mentioned nitrogen-doped Ginkgo biloba biomass fluorescent carbon quantum dots, the drying time in step 1 is 5 h.
[0017] In the above-mentioned nitrogen-doped Ginkgo biloba biomass fluorescent carbon quantum dots, the sieve mesh size in step 1 is 100 mesh.
[0018] In the above-mentioned nitrogen-doped Ginkgo biloba biomass fluorescent carbon quantum dots, the reaction feed ratio in step 2 is 1:1.
[0019] In the above-mentioned nitrogen-doped Ginkgo biloba biomass fluorescent carbon quantum dots, step 3 involves a hydrothermal reaction at 200°C for 8 hours.
[0020] In the above-mentioned nitrogen-doped Ginkgo biloba biomass fluorescent carbon quantum dots, step 4 involves centrifugation at 4000 rpm for 10 min.
[0021] In the above-mentioned nitrogen-doped Ginkgo biloba biomass fluorescent carbon quantum dots, step 5 uses a dialysis bag with a specification of 500 Da and an ultrapure water volume of 2 L.
[0022] In the above-mentioned nitrogen-doped Ginkgo biloba biomass fluorescent carbon quantum dots, in step 6, the freeze-drying temperature is -49℃ and the time is 24 h.
[0023] The third aspect of the present invention provides the application of the above-mentioned biomass fluorescent carbon quantum dots as fluorescent probes in the detection of Cr(VI).
[0024] The above application includes the following steps:
[0025] Step 1: Within the range of 0~251 μM, take 0.2 mL of Cr(VI) solution of different concentrations, add 0.2 mL of 0.2 mg / mL fluorescent carbon quantum dots and 0.6 mL of ultrapure water, and after mixing evenly, react for 2 min.
[0026] Step 2: Place the mixed solution obtained in Step 1 into a fluorescence spectrometer, select 420 nm as the excitation wavelength, set the spectral range to 300~700 nm, and after obtaining the complete fluorescence spectrum, read the fluorescence intensity value F at 514 nm.
[0027] Step 3: Measure 0.2 mL of ultrapure water and add it to 0.2 mL of the above-mentioned fluorescent carbon quantum dots at a concentration of 0.2 mg / mL and 0.6 mL of ultrapure water. After mixing evenly, react for 2 min.
[0028] Step 4: Place the mixed solution obtained in Step 3 into a fluorescence spectrometer, select 420 nm as the excitation wavelength, set the spectral range to 300~700 nm, and after obtaining the complete fluorescence spectrum, read the fluorescence intensity value F0 at 514 nm.
[0029] The linear regression equations for Cr(VI) concentrations in the ranges of 0–87 μM and 118–251 μM are as follows:
[0030] y = 1.00912 - 0.00364x, R 2 =0.992; y = 0.89053 - 0.00274x, R 2 =0.992
[0031] Following the method in steps 1-4, take a Cr(VI) solution of unknown concentration, obtain fluorescence intensity values F and F0, and calculate the concentration of Cr(VI) according to the linear equation.
[0032] The beneficial effects of this invention are:
[0033] Compared with the prior art, the advantages of the present invention are as follows: (1) The present invention is the first to use ginkgo leaves as carbon source and m-phenylenediamine as nitrogen source to prepare long-emission wavelength fluorescent carbon nanomaterials that exhibit green fluorescence under a 365 nm ultraviolet lamp. (2) Ginkgo leaves are natural agricultural and forestry wastes, which are widely available, cost-free, green and renewable, and free from secondary pollution. They replace traditional chemical synthesis carbon sources, and the preparation process is green, environmentally friendly, and low-cost. With the addition of m-phenylenediamine for precise nitrogen doping modification, the surface functional groups and electronic structure of carbon quantum dots can be effectively controlled, greatly improving the fluorescence quantum yield and optical stability of the material. The material has excellent fluorescence performance and strong storage stability, effectively solving the technical pain points of weak fluorescence and poor stability of traditional carbon quantum dots. (3) The present invention constructs a unique platform for tracking Cr(VI). The prepared nitrogen-doped fluorescent carbon quantum dots based on Ginkgo biloba biomass are rich in active functional groups such as amino and hydroxyl groups, which can undergo specific electron transfer with Cr(VI), thereby achieving specific identification of Cr(VI) in water. The fluorescence signal of the carbon quantum dots exhibits a regular quenching change with the increase of Cr(VI) concentration. Based on the good linear fitting relationship between fluorescence intensity and ion concentration, rapid and accurate quantitative analysis of Cr(VI) in water samples can be completed, and it has strong anti-interference ability. Attached Figure Description
[0034] Figure 1 Schematic diagram of the preparation of fluorescent carbon quantum dots and the detection of Cr(VI);
[0035] Figure 2 This is a transmission electron microscope image of the carbon quantum dots prepared in this invention;
[0036] Figure 3 Fourier transform infrared spectrum of fluorescent carbon quantum dots prepared in this invention;
[0037] Figure 4 The fluorescence spectra of the fluorescent carbon quantum dots prepared in this invention at different excitation wavelengths are shown.
[0038] Figure 5 The optimal excitation, emission, and ultraviolet spectra of the fluorescent carbon quantum dots prepared in this invention are shown.
[0039] Figure 6 The fluorescence intensity diagram shows the stability of the fluorescent carbon quantum dots prepared in this invention. The stability of the carbon quantum dots at different times (A), different salt concentrations (B), and different pH values (C) was tested.
[0040] Figure 7 The graph shows the fluorescence intensity variation of the fluorescent carbon quantum dots prepared in this invention under different interfering substances.
[0041] Figure 8The graph shows the change in relative fluorescence intensity of the fluorescent carbon quantum dots prepared in this invention after the addition of Cr(VI) in the presence of other interfering substances.
[0042] Figure 9 The fluorescence intensity changes of the fluorescent carbon quantum dots Y-NCDs prepared for this invention under different Cr(VI) amounts;
[0043] Figure 10 Linear relationship between Cr(VI) concentration increase and quenching efficiency;
[0044] Specific implementation methods
[0045] The present invention will be further illustrated by specific examples below. The present invention is not limited to the embodiments described, and minor variations may be made without departing from the scope thereof.
[0046] Example 1: Preparation method of nitrogen-doped Ginkgo biloba leaf biomass fluorescent carbon quantum dots
[0047] The preparation method is as follows, such as Figure 1 As shown in (a):
[0048] Step 1: Take the cleaned ginkgo leaves and dry them in an oven at 110℃ for 5 hours to remove moisture. Then grind them into powder and sieve them (100 mesh).
[0049] Step 2: The hydrothermal preparation process of nitrogen-doped Ginkgo biloba biomass fluorescent carbon quantum dots was optimized using a three-factor, three-level orthogonal experiment. Hydrothermal temperature (factor A), reaction time (factor B), and the mass ratio of Ginkgo biloba raw material to amino-rich raw material (factor C) were selected as the core influencing factors. The fluorescence intensity of the product was used as the evaluation index, as shown in Table 1. Based on the results of the orthogonal experimental range analysis, the optimal reaction conditions were obtained as follows.
[0050] Step 3: Place the ginkgo leaf powder and m-phenylenediamine in a beaker at a mass ratio of 1:1 and disperse them evenly by ultrasonication.
[0051] Step 4: Transfer the above mixture to a Teflon-lined reactor and hydrothermally react at 200°C for 8 hours;
[0052] Step 5: Centrifuge the obtained dark yellow carbon quantum dot dispersion at 4000 rpm for 10 min and collect the supernatant;
[0053] Step 6: Place the obtained solution into a 500 Da dialysis bag, pour in 2 L of ultrapure water and dialyze to remove impurities, obtaining a yellow solution;
[0054] Step 7: Place the obtained solution in a vacuum freeze dryer at -49°C for 24 h to obtain purified carbon quantum dot powder.
[0055] Table 1. Orthogonal experimental design and results
[0056]
[0057] Example 2 Characterization based on nitrogen-doped Ginkgo biloba leaf biomass fluorescent carbon quantum dots
[0058] The specific characterization results are as follows:
[0059] (1) such as Figure 2 As shown, the nitrogen-doped Ginkgo biloba biomass fluorescent carbon quantum dots (Y-NCDs) were characterized by transmission electron microscopy, and their size was found to be 3.15 ± 0.019 nm.
[0060] (2) For example Figure 3 As shown, the relevant functional groups of the prepared Y-NCDs were characterized by Fourier transform infrared spectroscopy. (3430 cm⁻¹) -1 The peak at 1620 cm⁻¹ corresponds to the stretching vibration of OH / NH. -1 The peak at 1384 cm⁻¹ is attributed to the stretching vibration of C=O. -1 The peak at 750 cm⁻¹ corresponds to the stretching vibration of COC. -1 The peak at the specified location confirms the presence of CN. Infrared spectroscopy analysis results indicate that the surface of Y-NCDs contains various nitrogen and oxygen functional groups, including hydroxyl, carboxyl, amino, and carbonyl groups.
[0061] (3) To study the optical properties of Y-NCDs, the fluorescence spectra of Y-NCDs were recorded (e.g., Figure 4 Fluorescence emission spectra of Y-NCDs at different excitation wavelengths in the range of 370–480 nm (measured every 10 nm), such as... Figure 4 As shown, the fluorescence emission intensity of Y-NCDs first increases and then decreases, exhibiting no fluorescence dependence, which is related to their uniform particle size and surface states. The optimal excitation wavelength is 420 nm, and the optimal generation wavelength is 514 nm. Y-NCDs exhibit bright green fluorescence under 365 nm UV illumination, and a distinct absorption peak at 275 nm can be observed in the UV absorption spectrum. This may be due to n-π* transitions of the C=O bond and π-π* transitions of the C=C bond (e.g., ...). Figure 5 ).
[0062] (4) The stability of Y-NCDs under different times, salt concentrations and pH values was tested. The fluorescence intensity of Y-NCDs did not change much under different conditions, indicating that Y-NCDs have good stability (e.g., Figure 6 ). Figure 6 (A) shows that when Y-NCDs are continuously irradiated with a 365 nm UV lamp for 60 min, their fluorescence intensity remains stable. Figure 6(B) In the salt resistance test, even when the NaCl concentration was as high as 1.0 M, the fluorescence intensity of Y-NCDs did not fluctuate significantly, showing good salt resistance. The stability of nanoparticles is one of the main contributions to improving the accuracy of chemical detection or biosensors. Figure 6 (C) shows that the fluorescence intensity of Y-NCDs does not change significantly when the solution is in the pH range of 4–11, but the fluorescence intensity decreases under strong acid and strong alkaline conditions. The results indicate that Y-NCDs have good pH tolerance and can be used over a wide pH range.
[0063] Example 3: Detection of Cr(VI) based on nitrogen-doped Ginkgo biloba biomass fluorescent carbon quantum dots as fluorescent probes
[0064] The specific testing method includes the following steps:
[0065] To test whether fluorescent carbon quantum dots have good selectivity, anions and ions that may exist in the water environment were selected as potential interfering ions.
[0066] Step 1: Take 0.2 mL of the anion and ion interfering ion or Cr(VI) test solution respectively, add 0.2 mL of 0.2 mg / mL fluorescent carbon quantum dots prepared in Example 1 and 0.6 mL of ultrapure water, and after mixing evenly, react for 2 min;
[0067] Step 2: Place the mixed solution obtained in Step 1 into a fluorescence spectrometer, select 420 nm as the excitation wavelength, set the spectral range to 300~700 nm, and after obtaining the complete fluorescence spectrum, read the fluorescence intensity value F at 514 nm.
[0068] Step 3: Measure 0.2 mL of ultrapure water and add it to 0.2 mL of 0.2 mg / mL fluorescent carbon quantum dots prepared in Example 1 and 0.6 mL of ultrapure water. After mixing evenly, react for 2 min.
[0069] Step 4: Place the mixed solution obtained in Step 3 into a fluorescence spectrometer, select 420 nm as the excitation wavelength, and set the spectral range to 300~700 nm. After obtaining the complete fluorescence spectrum, read the fluorescence intensity value F0 at 514 nm. The detection process is as follows: Figure 1 As shown in (b).
[0070] In the absence of Cr(VI), compared with F and F0, all potential anionic and cation interfering ions had no significant effect on the fluorescence intensity of carbon quantum dots, and the fluorescence intensity of Cr(VI)-containing Y-NCDs was much lower than that of the blank sample. This demonstrates that only Cr(VI) can effectively quench the fluorescence of Y-NCDs, indicating that Y-NCDs have excellent selectivity for Cr(VI) (e.g., ...). Figure 7 ).
[0071] Considering the complexity of actual samples, it is necessary to further investigate the effect of interfering substances (M) on the Y-NCDs and Cr(VI) system through interference experiments.
[0072] Step 1: Measure 0.2 mL of the interfering substance (M) and the test solution (M represents Al) respectively. 3+ Ba 2+ Ca 2+ Co 2+ K + Mg 2+ Mn 2+ Na + NH4 + Ni 2+ Pb 2+ Zn 2+ Cl - I - NO2 - SO3 2- SO4 2- ,Br - OH - Add 0.2 mL of 0.2 mg / mL fluorescent carbon quantum dots prepared in Example 1 and 0.4 mL of ultrapure water to the mixture, and after mixing evenly, react for 2 min.
[0073] Step 2: Place the mixed solution obtained in Step 1 into a fluorescence spectrometer, select 420 nm as the excitation wavelength, set the spectral range to 300~700 nm, and after obtaining the complete fluorescence spectrum, read the fluorescence intensity value F at 514 nm.
[0074] Step 3: Take 0.2 mL of the interfering substance (M) test solution and 0.2 mL of Cr(VI) solution, and add them to 0.2 mL of 0.2 mg / mL fluorescent carbon quantum dots prepared in Example 1 and 0.6 mL of ultrapure water. After mixing evenly, react for 2 min.
[0075] Step 4: Place the mixed solution obtained in Step 3 into a fluorescence spectrometer, select 420 nm as the excitation wavelength, set the spectral range to 300~700 nm, and after obtaining the complete fluorescence spectrum, read the fluorescence intensity value F0 at 514 nm.
[0076] In the presence of Cr(VI), compared to F and F0, when other interfering ions coexist with Cr(VI), none of the interfering ions react with Cr(VI), and there is no significant interference to the Y-NCDs and Cr(VI) sensing system. Cr(VI) can still effectively quench the Y-NCDs solution, indicating that Y-NCDs have excellent anti-interference ability in complex and variable environments (e.g., Figure 8 ).
[0077] Different concentrations (0~251 μM) of Cr(VI) were added to carbon quantum dots. Figure 9 The fluorescence intensity changes of Y-NCDs under different Cr(VI) concentrations are shown. Within the range of 0–251 μM, fluorescence quenching showed a good linear relationship with increasing Cr(VI) concentration. The linear regression equations for Cr(VI) concentration ranges of 0–87 μM and 118–251 μM were: y = 1.00912 -0.00364x, R0 2 =0.992; y = 0.89053 - 0.00274x, R 2 =0.992, which allows for the quantitative detection of Cr(VI) (e.g. Figure 10 ).
[0078] In summary, the nitrogen-doped Ginkgo biloba biomass carbon quantum dots prepared in this invention are synthesized in one step via a hydrothermal method, exhibit stable fluorescence properties, and are non-toxic. The functional fluorescent carbon quantum dots of this invention can be used as fluorescent probes for the quantitative measurement of Cr(VI).
Claims
1. A fluorescent carbon quantum dot based on nitrogen-doped Ginkgo biloba leaf biomass, characterized in that, The preparation method includes the following steps: Step 1: After washing the ginkgo leaves, dry them in an oven at a specific temperature for a certain period of time, then grind them into powder and sift them. Step 2: Mix ginkgo leaf powder with amino-rich raw materials at a certain feeding ratio, and then ultrasonically disperse the mixture evenly. Step 3: Transfer the above mixture to a Teflon-lined reactor for hydrothermal reaction; Step 4: Centrifuge the obtained dark yellow carbon quantum dot dispersion and collect the supernatant; Step 5: Place the obtained solution into a dialysis bag, pour in ultrapure water and dialyze to remove impurities, obtaining a yellow solution; Step 6: Place the obtained solution in a vacuum freeze dryer to obtain purified nitrogen-doped Ginkgo biloba biomass fluorescent carbon quantum dots.
2. The fluorescent carbon quantum dots based on nitrogen-doped Ginkgo biloba leaf biomass according to claim 1, characterized in that, In step 1, the drying temperature is 110℃, the drying time is 5 hours, and the sieve mesh size is 100 mesh.
3. The fluorescent carbon quantum dots based on nitrogen-doped Ginkgo biloba leaf biomass according to claim 1, characterized in that, In step 2, the mass ratio of the ginkgo leaf powder to the amino-rich raw material is 1:1, and the amino-rich raw material is one or more of o-phenylenediamine, m-phenylenediamine, and p-phenylenediamine.
4. The fluorescent carbon quantum dots based on nitrogen-doped Ginkgo biloba leaf biomass according to claim 1, characterized in that, In step 3, the hydrothermal reaction is carried out at 160℃-200℃ for 4-8 hours.
5. The fluorescent carbon quantum dots based on nitrogen-doped Ginkgo biloba leaf biomass according to claim 1, characterized in that, In step 4, the centrifugation is performed at 4000 rpm for 10 min.
6. The fluorescent carbon quantum dots based on nitrogen-doped Ginkgo biloba leaf biomass according to claim 1, characterized in that, In step 5, the dialysis bag used is 500 Da, and the amount of ultrapure water used is 2 L.
7. The fluorescent carbon quantum dots based on nitrogen-doped Ginkgo biloba leaf biomass according to claim 1, characterized in that, In step 6, the freeze-drying temperature is -49°C and the time is 24 hours.
8. The application of nitrogen-doped Ginkgo biloba biomass fluorescent carbon quantum dots as described in any one of claims 1-7 in the quantitative measurement of Cr(VI) using fluorescent probes.
9. The application according to claim 8, characterized in that, Includes the following steps: Step 1: Within the range of 0~251 μM, take 0.2 mL of Cr(VI) solution of different concentrations, add 0.2 mL of 0.2 mg / mL of nitrogen-doped Ginkgo biloba biomass fluorescent carbon quantum dots as described in any one of claims 1-7 and 0.6 mL of ultrapure water, and after mixing evenly, react for 2 min. Step 2: Place the mixed solution obtained in Step 1 into a fluorescence spectrometer, select 420 nm as the excitation wavelength, set the spectral range to 300~700 nm, and after obtaining the complete fluorescence spectrum, read the fluorescence intensity value F at 514 nm. Step 3: Measure 0.2 mL of ultrapure water and add it to 0.2 mL of nitrogen-doped Ginkgo biloba biomass fluorescent carbon quantum dots based on any one of claims 1-7 and 0.6 mL of ultrapure water. After mixing evenly, react for 2 min. Step 4: Place the mixed solution obtained in Step 3 into a fluorescence spectrometer, select 420 nm as the excitation wavelength, set the spectral range to 300~700 nm, and after obtaining the complete fluorescence spectrum, read the fluorescence intensity value F0 at 514 nm. The linear regression equations for Cr(VI) concentrations in the ranges of 0–87 μM and 118–251 μM are as follows: y = 1.00912 - 0.00364x,R 2 =0.992;y = 0.89053 - 0.00274x,R 2 =0.992 Following the method in steps 1-4, take a Cr(VI) solution of unknown concentration, obtain fluorescence intensity values F and F0, and calculate the concentration of Cr(VI) according to the linear equation.